2020
DOI: 10.1108/jeas-01-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Globalisation, income inequality and poverty relationships: evidence from Mexico, Indonesia, Nigeria and Turkey

Abstract: PurposeThe study examines the dynamic relationship among globalisation, income inequality and poverty in Mexico, Indonesia, Nigeria and Turkey (MINT countries) between 1980 and 2018.Design/methodology/approachA Bayesian vector autoregressive (BVAR) approach is used as a technique of estimation hanging on the fact that the method uses prior distribution for the estimated parameters.FindingsThe results show that globalisation is a strong predictor of itself in all the MINT countries only in the short run. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This finding is similar to Fosu (2017), who found that poverty-inequality elasticity is higher than poverty-income elasticity. Similar to Osinubi and Olomola (2020), the Gini index exhibit no significant impact on poverty across all model specifications.…”
Section: Pooled Ols Resultsmentioning
confidence: 75%
“…This finding is similar to Fosu (2017), who found that poverty-inequality elasticity is higher than poverty-income elasticity. Similar to Osinubi and Olomola (2020), the Gini index exhibit no significant impact on poverty across all model specifications.…”
Section: Pooled Ols Resultsmentioning
confidence: 75%
“…The variables used in the study are measured as follows: different variables are used as measures of poverty in empirical studies. Headcount-based data for the poor (Omar and Inaba, 2020;Baloch et al, 2020;Kousar and Shabbir, 2021;Solarin, 2021;Ogbeide-Osaretin, 2021), income (Adekoya, 2018), infant mortality (Tsaurai, 2018;Magombeyi and Odhiambo, 2018;Khobai, 2021;Solarin, 2021), life expectancy (Magombeyi and Odhiambo, 2018;Tsaurai, 2018), multidimensional poverty index (Aziz et al, 2020;Osinubi and Olomola, 2020) and human development index (Nwani and Osuji, 2020) are used as proxy for poverty in some studies. Some other studies used per capita consumption expenditure as proxy for poverty due to the lack of data on poverty (Quartey, 2008;Odhiambo, 2009;Odhiambo, 2011;Nayasha, Gwenhure and Odhiambo, 2017;Sehrawat and Giri, 2018;Adeleye et al, 2020;Dada and Fanowopo, 2020;Garidzirai and Matiza, 2020).…”
Section: Datamentioning
confidence: 99%
“…The study interpolates for missing data in Nigeria in 2004 for TOE and 2017-2018 for TOA. Following the purpose of this study, an index, Tourism activity index (TOI), is generated from the three measures of tourism (TOA, TOE and TOR) using a principal component analysis (PCA (Osinubi & Olomola, 2020a) and (ii) Nigeria has the lowest TOA, while turkey has the highest TOA among the MINT countries. The variables are described in Table 2.…”
Section: Description Of Datamentioning
confidence: 99%
“…Tourism, however, though well established and thriving in More Developed Countries (MDCs), has yet to hit its full potential in MINT countries. MINT countries are an agglomeration of Mexico, Indonesia, Nigeria and Turkey; and are so-called due to their vast demographic and economic similarities such as having speedily growing and emerging economies, burgeoning populations, high labour force figures, single-digit growth rates, significant poverty levels and reliance on western technology (Durotoye, 2014;Kokotovic & Kurecic, 2016;Olomola & Osinubi, 2018;Osinubi, 2020a;2020b;Osinubi & Olomola, 2020a;2020b). Osinubi (2020a) and Ajani and Kalu (2017) submit that strong economic growth and greater returns on investment are expected of MINT countries within the next decade.…”
Section: Introductionmentioning
confidence: 99%